DEVELOPING ELECTRONIC MATHEMATICS MODUL ON THREE VARIABLES LINEAR EQUATION SYSTEM BASED ON SCIENTIFIC METHOD - Fitri Dami Ristanti; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Teaching materials in the learning process can help students understand mathematical concepts and attract students' attention to schools' availability. This research aims to develop an electronic module material. By using canker sores. By using the appropriate system. This research development using the ADDIE method consists of Analysis, Design, Development, Implementation, and Evaluation. This study's subjects are material validator, media validator, and pupils of SMAN 1 Welahan and SMAN 1 Pecangaan district Jepara. The technique of data accumulation were interviews, questionnaires, and documentation. The data analysis technique used quantitative analysis was converted into a qualitative Likert scale. Result of research SPLTV material module electronic development for SMA / MA class X with the scientific method. Revised electronic module validation to 3 material experts with an average score of 74.67 from 90, then presentation 82,967%. Three media experts used a module quality research instrument sheet with an average score of 108,67 from 125. The percentage was 86,936%. Five students in the test are limited to SMAN 1 Pecangaan, five students of State Senior High School (SMAN) 1 Welahan, 33 students of SMAN 1 Pecangaan, and 33 students of SMAN 1 Welahan in-class test to measure student response to electronic module With the average score of students' SMAN 1 Welahan student response scores was 100,657 from 125 then the percentage was 80.526%. The student response rating of SMAN 1 Welahan was 93,388 from 125, and then the present rate was 74.7104%. This research has successfully developed an electronic module with good quality (B), with a score of 377,385 from 465 and a percentage of idealization equal to 81,158%. Based on the assessment, the electronic module has suitable for use as a module for students.